-













































: ()

: ()

. .

1.

CnH2n

CH4-

612-

1022-

CnH2n

612-

36-

48-

CnH2n

24-

612-

48-

CnH2N-2

38-

34-

610-

CnH2N-2

34-

46-

712-

CnH2n-6

66-

78-

810-

2.

)

sp3 -

sp3 -

sp2-

sp- sp-

sp2-

) ∟ 109*28' ∟ 60*, 90*, 100*, 120* ∟120* ∟ 120* ∟ 180* ∟ 120*
) () 0,154 0,154 0,134 0,134 0,12 0,142
)
)

H

H C H ()

H

CH2

CH2---------CH2 ()

͠ H

C=C

H H ()

CH2=C=CH2 ( 1,2)

HC≡CH ()

CH

CH ()

HC

HC CH

CH

3.

1.

!

)

1) H3C-CH2-CH2-CH3 ()

2)H3C-CH-CH3

CH3 (2 )

1) CH2-CH-CH3

CH2-CH2 ( )

1) CH2=CH-CH2-CH3 ( 1)

2) CH2=C-CH3

CH3 ( 1)

1)CH2=C=CH-CH2-CH3 ( 1,2)

2)CH2=C=C-CH3

CH3 (21,2)

1)CH≡C-CH2-CH2-CH3 ( 1)

2)CH≡C-CH-CH3

CH3 (21)

1)

CH3

CH3 -

2) CH3


CH3 -

3) CH3

-

CH3

) ()

CH2=CH-CH2-CH3 ( 1)

CH3-CH=CH-CH3 (2)

1)CH2=C=CH-CH2-CH3 ( 1,2)

2)CH3=CH-CH=CH-CH3 ( 1,3)

1)CH≡C-CH2-CH3 ( 1)

2)CH3-C≡C-CH3 ( 2)

)

1) 蠠 2)

CH CH2=CH-CH3

CH--------CH ()

()

( ) ( )

:

1) CH2=C=CH2 ()

2) CH≡C-CH3 ()

)

1) CH2-CH-CH3 2)CH2-CH-CH3

CH2-CH-CH3 CH3-CH-CH2

(1,2) (1,3)

2.

) (- )

CH3 CH3 CH3 H

C=C C=C

H () H H () CH3

CH3 CH=CH2 CH3 H

C=C C=C

H H H CH=CH2

3. .

)

CH4+O2→CO2+H2O+Q

CH2

CH2-----CH2+O2→CO2+H2O+Q

2H4+O2→CO2+H2O+Q

2 !

1.

2C2H2+5O2→4CO2+2H2O+Q

2

2H2+O2→C+H2O

1.

C6H6 +O2→CO2+H2O

2.

C6H6+O2→C+H2O+Q

)

C4H10→4C+5H2+Q

2H4→C+H2-Q

1. CH2=CH-CH=CH2+H2→

CH2-CH=CH-CH2

2

H H

2. CH3-CH=CH=CH3+H2→

2

CH3-(CH2)2-CH3

C2H2→C+H2

C6H6→C+H2-Q

)

*CH4+CL2→CH3CL+HCL

*CH3CL+CL2→CH2CL2+HCL

*CH2CL2+CL=CHCL3+HCL

*CHCL3+CL2→CCL4+HCL

C7H14+Br2→C7H13Br+HBr ()

1. C6H6+CL2→C6H5-CL

2.C6H6+HNO3→C6H5-NO3

)

(+H2, +H HAL ,+HAL2, +H2O)

CH3-CH2-CH2-CH3→

CH3-CH-CH3

CH3 (2 )

CH

CH2CH2+H2→CH3-CH2-CH3 ()

H2

CH2---CH2+Br2→CH2+CH2+CH2

(1,3) Br Br

*CH2=CH2+H2→CH3+CH3

*2H4+HOH→CH3-CH2OH

*C2H4+HCL→CH3-CH2CL

*C2H4+CL2→CH2CL-CH2CL

2 : ≡→=→-

1. CH≡CH+2H2→CH3-CH3

2. H≡CH+2CL2→

CHCL2-CHCL2 (1122)

3. C2H2+2HCL→CH2CL=CH2CL

1,2

4. C2H2+H2O→CH3-C=O

H ()

1.

C6H6+3H2→C6H12 ()

2.C6H6+3CL2→C6H5CL

)

*22H4+O2→2CH2-CH2

O

n(CH2=CH-CH=CH2) →

(-CH2-CH=CH-CH2-)n

3C2H2→C6H6 ()


2012 , .